THE UPWARDS AND DRAWBACK OF TECHNICAL DEVICES IN EDUCATIONAL SYSTEM (International Conference on Educational Discoveries and Humanities, 2025)
This research paper explores both the advantages and disadvantages of using technical devices in the educational system. In modern education, technology has become a key tool that enhances learning experiences, promotes interactive teaching, and improves access to educational resources. Devices such as computers, tablets, and smartboards help teachers create more engaging lessons and enable students to develop digital literacy and problem-solving skills. However, the overreliance on technology also brings certain drawbacks, including distractions, reduced face-to-face interaction, and unequal access to digital tools. The study emphasizes the need for balanced integration of technology in education to ensure that it supports rather than replaces traditional teaching methods.